DIGITAL MARKETING COMMUNICATION MODEL BASED ON AQUA SUSTAINABILITY PRODUCTS - Daniel Susilo; I Gusti Ngurah Sarjana (Lafadz Jaya Publisher, 2023)
Aqua is mineral water product that has been friendly with Indonesians since long ago. They provide interesting nature promotion since Indonesian loves anything close to nature, it makes them trust the product of Aqua. As a trusted product with long sustainability, it will be an important data to analyse about Aqua. This paper used content analysis by Krippendorf to analyse the digital marketing communication from Aqua. The concept used by Aqua brand, that they use the Masaru Emoto product at branding their water being finding of the research. Water is plain, but with the nature aesthetic and famous Emoto’s pseudo-science, it attracts their audience to put long trust on them.